2015
DOI: 10.2310/7750.2014.14051
|View full text |Cite
|
Sign up to set email alerts
|

Acitretin-Induced Hepatitis: When to Monitor Cholestatic Enzymes

Abstract: This is the first literature review on acitretin-induced hepatitis. Although acitretin-induced hepatoxicity is rare, the seemingly unusual presentation of a mixed pattern of hepatocyte injury and cholestasis may be more common than previously thought. The findings should encourage clinicians not only to monitor transaminases but also to consider measuring cholestatic enzymes (ALP/GGT) in patients with transaminase abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Adverse effects to the liver are the reason for regular laboratory tests especially in the beginning of therapy. Reported prevalences of transaminase elevation during acitretin treatment range from less than 1 to up to 16% [9]. Marked elevations (> 3 × ULN) are estimated to occur in 1-5% of acitretin-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects to the liver are the reason for regular laboratory tests especially in the beginning of therapy. Reported prevalences of transaminase elevation during acitretin treatment range from less than 1 to up to 16% [9]. Marked elevations (> 3 × ULN) are estimated to occur in 1-5% of acitretin-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Liver diseases are neither uncommon in psoriasis patients [40] nor absolute contraindications of acitretin treatment. Nevertheless, studies have demonstrated hepatobiliary toxicity with acitretin therapy because of hepatic mitochondrial dysfunction and sinusoidal congestion [41]. Although such liver injury is infrequent and transient, persistent elevation of liver enzymes has been reported in the setting of preexisting liver diseases [41].…”
Section: Risk Of Psychiatric Disorders and Acitretinmentioning
confidence: 99%
“…Nevertheless, studies have demonstrated hepatobiliary toxicity with acitretin therapy because of hepatic mitochondrial dysfunction and sinusoidal congestion [41]. Although such liver injury is infrequent and transient, persistent elevation of liver enzymes has been reported in the setting of preexisting liver diseases [41]. In addition, the metabolism of acitretin primarily takes place in the liver, followed by drug elimination partly through the bile [42].…”
Section: Risk Of Psychiatric Disorders and Acitretinmentioning
confidence: 99%